Solid-state secondary battery and electric device

By using a porous electrolyte membrane and conductive layer in the composite electrode sheet of a solid-state secondary battery, the contact impedance problem caused by interface incompatibility of solid-state secondary batteries is solved, and its cycling performance and rate performance are significantly improved.

CN119481323APending Publication Date: 2025-02-18NINGDE AMPEREX TECHNOLOGY LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411719341.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The contact impedance increase caused by the incompatibility of the internal interface during the cycle of solid-state secondary batteries affects the expansion rate and capacity retention rate.

Method used

By introducing a porous electrolyte membrane and a conductive layer into the composite electrode sheet, it is ensured that the porous electrolyte membrane contains the same polymer as the positive electrode material layer and the negative electrode material layer, reducing the interface gap and reducing the contact impedance.

Benefits of technology

It effectively improves the expansion rate and capacity retention rate during the circulation of solid-state secondary batteries, and improves the rate performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481323A_ABST
    Figure CN119481323A_ABST
Patent Text Reader

Abstract

The invention provides a solid-state secondary battery and an electric device, the solid-state secondary battery comprises a composite pole piece, the composite pole piece comprises a positive electrode material layer, a negative electrode material layer and a composite current collector located between the positive electrode material layer and the negative electrode material layer, the composite current collector comprises a porous electrolyte membrane as well as a first conductive layer and a second conductive layer which are respectively positioned on two surfaces of the porous electrolyte membrane; the porous electrolyte membrane comprises a solid electrolyte, a polymer and an electrolyte salt, and the positive electrode material layer and / or the negative electrode material layer comprise the polymer. The porous electrolyte membrane and the positive electrode material layer and / or the negative electrode material layer contain the same polymer, so that the gaps between the positive electrode material layer and the composite current collector and between the negative electrode material layer and the composite current collector can be reduced, and the contact impedance of the solid-state secondary battery can be reduced; therefore, the expansion rate and the capacity retention rate of the solid-state secondary battery in the circulating process are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemical technology, and in particular to a solid-state secondary battery and an electrical device. Background Art

[0002] At present, most secondary batteries use organic liquid electrolytes, which inevitably introduce volatile, flammable, and explosive organic liquids into the secondary battery system, bringing serious safety hazards to the secondary battery system. Therefore, replacing the electrolyte with a solid electrolyte and developing a solid-state secondary battery is the only way to fundamentally solve the safety problem.

[0003] Solid-state secondary batteries often face the problem of incompatibility between internal interfaces during use. Specifically, due to the inherent properties of the solid-solid interface, the gap between two adjacent interfaces is large, the contact impedance of the solid-state secondary battery increases, and the expansion rate and capacity retention rate of the solid-state secondary battery during the cycle process are affected. The current solution to the solid electrolyte interface problem focuses on researching solid electrolytes with better flexibility and improving the interface contact between the positive and negative electrode material layers, but it is difficult to solve this problem from the root. Summary of the invention

[0004] The purpose of this application is to provide a solid-state secondary battery and an electrical device to improve the expansion rate and capacity retention rate of the secondary battery during the cycle process. The specific technical solution is as follows: The first aspect of the present application provides a solid-state secondary battery, which includes a composite electrode sheet, the composite electrode sheet includes a positive electrode material layer, a negative electrode material layer and a composite current collector located between the positive electrode material layer and the negative electrode material layer, the composite current collector includes a porous electrolyte membrane and a first conductive layer and a second conductive layer respectively located on the two surfaces of the porous electrolyte membrane; the porous electrolyte membrane includes a solid electrolyte, a polymer and an electrolyte salt, and the positive electrode material layer and / or the negative electrode material layer contain the polymer. The present application can reduce the gap between the positive electrode material layer and the composite current collector and / or the negative electrode material layer and the composite current collector by making the porous electrolyte membrane and the positive electrode material layer and / or the negative electrode material layer contain the same polymer, which is beneficial to reduce the contact impedance of the solid-state secondary battery, thereby improving the expansion rate and capacity retention rate during the solid-state secondary battery cycle. In addition, the gap is reduced, the transmission path of the active ions becomes shorter, and it is also beneficial to further improve the rate performance of the solid-state secondary battery.

[0005] In some embodiments of the present application, the polymer is selected from at least one of polyvinylidene fluoride, polyethylene oxide, polyacrylonitrile or polymethyl methacrylate. The present application can reduce the gap between the positive electrode material layer and the composite current collector, the negative electrode material layer and the composite current collector by making the porous electrolyte membrane and the positive electrode material layer and / or the negative electrode material layer contain the same polymer, which is beneficial to reduce the contact impedance of the solid-state secondary battery, thereby improving the expansion rate and capacity retention rate during the solid-state secondary battery cycle. In addition, the gap is reduced, the transmission path of the active ions becomes shorter, and it is also beneficial to further improve the rate performance of the solid-state secondary battery.

[0006] In some embodiments of the present application, based on the mass of the porous electrolyte membrane, the mass percentage W1 of the solid electrolyte is 10% to 50%, the mass percentage W2 of the polymer is 40% to 80%, and the mass percentage W3 of the electrolyte salt is 10% to 20%. By regulating the mass percentage W1 of the solid electrolyte, the mass percentage W2 of the polymer, and the mass percentage W3 of the electrolyte salt within the above range, the obtained porous electrolyte membrane has high ionic conductivity and good mechanical strength, which can provide a channel for the transmission of ions on the one hand, and provide support for the first conductive layer, the second conductive layer, the positive electrode material layer, and the negative electrode material layer on the other hand.

[0007] In some embodiments of the present application, the solid electrolyte is selected from at least one of an oxide solid electrolyte, a sulfide solid electrolyte, a halide solid electrolyte, a NASICON solid electrolyte or a perovskite solid electrolyte. The above solid electrolyte has high ionic conductivity, which is conducive to improving the rate performance of the secondary battery.

[0008] In some embodiments of the present application, the average particle size D of the solid electrolyte is 0.001 μm to 3.5 μm. By regulating the average particle size D of the solid electrolyte within the above range, the obtained porous electrolyte membrane is conducive to improving the transmission efficiency of active ions, and the porous electrolyte membrane has good mechanical strength, which is conducive to improving the rate performance and structural stability of the solid-state secondary battery.

[0009] In some embodiments of the present application, the electrolyte salt is selected from at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, or lithium tetrafluoroborate.

[0010] In some embodiments of the present application, the porous electrolyte membrane satisfies at least one of the following features: (1) The thickness H1 of the porous electrolyte membrane is 1 μm to 4 μm; (2) The porosity P1 of the porous electrolyte membrane is 30% to 80%; (3) The average pore diameter d1 of the porous electrolyte membrane is 200 nm to 1 μm.

[0011] The porous electrolyte membrane satisfies at least one of the above characteristics, which is beneficial to improving the expansion rate and capacity retention rate during the cycle of the solid-state secondary battery, and further improving the rate performance of the solid-state secondary battery.

[0012] In some embodiments of the present application, the first conductive layer satisfies at least one of the following features: (1) The thickness H2 of the first conductive layer is 0.1 μm to 5 μm; (2) The porosity P2 of the first conductive layer is 10% to 75%; (3) The average pore diameter d2 of the first conductive layer is 0.1 μm to 0.8 μm.

[0013] The first conductive layer satisfies at least one of the above characteristics, which is beneficial to improving the expansion rate and capacity retention rate of the solid-state secondary battery during the cycle process, and further improving the rate performance of the solid-state secondary battery.

[0014] In some embodiments of the present application, the second conductive layer satisfies at least one of the following features: (1) The thickness H3 of the second conductive layer is 0.1 μm to 5 μm; (2) The porosity P3 of the second conductive layer is 10% to 75%; (3) The average pore diameter d3 of the second conductive layer is 0.1 μm to 0.8 μm.

[0015] The second conductive layer satisfies at least one of the above characteristics, which is beneficial to improving the expansion rate and capacity retention rate of the solid-state secondary battery during the cycle process, and further improving the rate performance of the solid-state secondary battery.

[0016] In some embodiments of the present application, the first conductive layer and the second conductive layer are each independently selected from a metal layer or a conductive carbon layer. The first conductive layer and the second conductive layer have good conductivity, and the obtained composite current collector also has good conductivity, which is conducive to improving the expansion rate and capacity retention rate during the cycle of the solid-state secondary battery.

[0017] In some embodiments of the present application, the solid-state secondary battery includes at least two stacked composite pole sheets, and a solid electrolyte is arranged between the two adjacent composite pole sheets; in the two adjacent composite pole sheets, the positive electrode material layer of one composite pole sheet is adjacent to the negative electrode material layer of the other composite pole sheet.

[0018] A second aspect of the present application provides an electrical device, which includes the solid-state secondary battery in any of the aforementioned embodiments.

[0019] Beneficial effects of this application: The present application provides a solid-state secondary battery, which includes a composite electrode sheet, the composite electrode sheet includes a positive electrode material layer, a negative electrode material layer and a composite current collector located between the positive electrode material layer and the negative electrode material layer, the composite current collector includes a porous electrolyte membrane and a first conductive layer and a second conductive layer located on two surfaces of the porous electrolyte membrane respectively; the porous electrolyte membrane includes a solid electrolyte, a polymer and an electrolyte salt, and the positive electrode material layer and / or the negative electrode material layer include a polymer. The present application reduces the gap between the positive electrode material layer and the composite current collector, and between the negative electrode material layer and the composite current collector by making the porous electrolyte membrane and the positive electrode material layer and / or the negative electrode material layer contain the same polymer, which is beneficial to reducing the contact impedance of the solid-state secondary battery, thereby improving the expansion rate and capacity retention rate during the solid-state secondary battery cycle. In addition, the gap is reduced, the transmission path of the active ions becomes shorter, and it is also beneficial to further improve the rate performance of the solid-state secondary battery.

[0020] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other embodiments can also be obtained based on these drawings.

[0022] Figure 1 It is a schematic diagram of the partial structure of a solid-state secondary battery in one embodiment of the present application. DETAILED DESCRIPTION

[0023] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.

[0024] The first aspect of the present application provides a solid-state secondary battery, such as Figure 1As shown, the solid-state secondary battery includes a composite electrode 10, the composite electrode includes a positive electrode material layer 11, a negative electrode material layer 12, and a composite current collector 13 located between the positive electrode material layer 11 and the negative electrode material layer 12, and the composite current collector 13 includes a porous electrolyte membrane 133 and a first conductive layer 131 and a second conductive layer 132 located on both surfaces of the porous electrolyte membrane 133. The first conductive layer 131 is arranged between the porous electrolyte membrane 133 and the positive electrode material layer 11, and the second conductive layer 132 is arranged between the porous electrolyte membrane 133 and the negative electrode material layer 12. It can be understood that the first conductive layer 131 can also be arranged between the porous electrolyte membrane 133 and the negative electrode material layer 12, and the second conductive layer 132 can be arranged between the porous electrolyte membrane 133 and the positive electrode material layer 11.

[0025] The solid-state secondary battery provided by the present application, wherein the composite electrode sheet comprises a porous electrolyte membrane, and material layers with opposite polarities are respectively arranged on both sides of the porous electrolyte membrane, so that the double-sided transmission of active ions (such as lithium ions) can be realized, and the active ion transmission path is halved compared to the traditional non-porous current collector, which is conducive to improving the rate performance of the solid-state secondary battery. Since the porous electrolyte membrane, the first conductive layer and the second conductive layer in the composite current collector are all porous, the contact between the positive electrode material layer and the composite current collector, and the negative electrode material layer and the composite current collector is not tight, and there is a gap, which leads to an increase in the contact impedance of the solid-state secondary battery, thereby affecting the expansion rate and capacity retention rate during the solid-state secondary battery cycle. Based on this, the present application can reduce the gap between the positive electrode material layer and the composite current collector, and the negative electrode material layer and the composite current collector by making the porous electrolyte membrane and the positive electrode material layer and / or the negative electrode material layer contain the same polymer, which is conducive to reducing the contact impedance of the solid-state secondary battery, thereby improving the expansion rate and capacity retention rate during the solid-state secondary battery cycle. In addition, the gap inside the secondary battery is reduced and the transmission path of active ions is shortened, which is also conducive to further improving the rate performance of the solid-state secondary battery.

[0026] In some embodiments of the present application, the porous electrolyte membrane includes a solid electrolyte, a polymer and an electrolyte salt, and the positive electrode material layer includes a polymer, that is, the porous electrolyte membrane and the positive electrode material layer include the same polymer. The production method of the solid-state secondary battery is usually to obtain an electrolyte material in a solid form between the pole pieces by in-situ curing at high temperature, and the porous electrolyte membrane and the positive electrode material layer include the same polymer. Before polymerization, the porous electrolyte membrane and the positive electrode material layer are infiltrated with unpolymerized solid electrolyte, and the composite current collector has a porous property. During the polymerization process, the gap between the positive electrode material layer and the composite current collector can be reduced by the interaction force between the polymers, which is conducive to improving the expansion rate and capacity retention rate during the cycle of the solid-state secondary battery, and further improving the rate performance of the solid-state secondary battery.

[0027] In some embodiments of the present application, the porous electrolyte membrane includes a solid electrolyte, a polymer and an electrolyte salt, and the negative electrode material layer includes a polymer, that is, the porous electrolyte membrane and the negative electrode material layer include the same polymer. Before polymerization, the porous electrolyte membrane and the negative electrode material layer are infiltrated by the unpolymerized solid electrolyte, and the composite current collector has a porous property. During the polymerization process, the gap between the negative electrode material layer and the composite current collector can be reduced by the interaction force between the polymers, thereby facilitating the improvement of the expansion rate and capacity retention rate during the solid-state secondary battery cycle, and further improving the rate performance of the solid-state secondary battery.

[0028] In some embodiments of the present application, the porous electrolyte membrane includes a solid electrolyte, a polymer and an electrolyte salt, and the positive electrode material layer and the negative electrode material layer include a polymer, that is, the porous electrolyte membrane, the positive electrode material layer and the negative electrode material layer include the same polymer. Before polymerization, the porous electrolyte membrane, the positive electrode material layer and the negative electrode material layer are infiltrated by the unpolymerized solid electrolyte, and the composite current collector has a porous property. During the polymerization process, the gap between the positive electrode material layer and the composite current collector, and the gap between the negative electrode material layer and the composite current collector can be reduced by the interaction force between the polymers, so that the gaps on both sides of the composite current collector are reduced, which is conducive to further improving the expansion rate and capacity retention rate during the solid-state secondary battery cycle, and further improving the rate performance of the solid-state secondary battery.

[0029] In some embodiments of the present application, the polymer is selected from at least one of polyvinylidene fluoride, polyethylene oxide, polyacrylonitrile or polymethyl methacrylate. By selecting the above polymers, the interaction force formed is stronger, which is more conducive to reducing the gap between the positive electrode material layer and the composite current collector, and the negative electrode material layer and the composite current collector, thereby further improving the expansion rate and capacity retention rate during the cycle of the solid-state secondary battery, and further improving the rate performance of the solid-state secondary battery. In some embodiments of the present application, the polymer is selected from at least one of polyethylene oxide (PEO), polyethylene glycol (PEG), and polyvinylidene fluoride (PVDF).

[0030] In some embodiments of the present application, based on the mass of the porous electrolyte membrane, the mass percentage W1 of the solid electrolyte is 10% to 50%, the mass percentage W2 of the polymer is 40% to 80%, and the mass percentage W3 of the electrolyte salt is 10% to 20%. For example, the mass percentage W1 of the solid electrolyte can be 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50% or a range consisting of any two values ​​therebetween. For example, the mass percentage W2 of the polymer can be 40%, 42%, 44%, 45%, 47%, 49%, 50%, 52%, 54%, 55%, 57%, 59%, 60%, 62%, 64%, 65%, 67%, 69%, 70%, 72%, 74%, 75%, 77%, 79%, 80% or a range consisting of any two values ​​therebetween. For example, the mass percentage content W3 of the electrolyte salt can be 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20% or a range consisting of any two values ​​therebetween. The solid electrolyte in the porous electrolyte membrane provides the porous electrolyte membrane with a higher ionic conductivity; the polymer in the porous electrolyte membrane is used to reduce the gap between the positive electrode material layer and the composite current collector, the negative electrode material layer and the composite current collector, and on the other hand, it can provide a higher mechanical strength for the porous electrolyte membrane; the electrolyte salt in the porous electrolyte membrane is used to provide active ions. By regulating the mass percentage content W1 of the solid electrolyte, the mass percentage content W2 of the polymer and the mass percentage content W3 of the electrolyte salt within the above range, the obtained porous electrolyte membrane has high ionic conductivity and good mechanical strength, which can provide a channel for the transmission of ions on the one hand, and provide support for the first conductive layer, the second conductive layer, the positive electrode material layer, and the negative electrode material layer on the other hand.

[0031] In some embodiments of the present application, the solid electrolyte is selected from at least one of an oxide solid electrolyte, a sulfide solid electrolyte, a halide solid electrolyte, a NASICON solid electrolyte, or a perovskite solid electrolyte. The above solid electrolytes have high ionic conductivity, and by selecting a solid electrolyte, it is beneficial to improve the rate performance of the secondary battery.

[0032] In the present application, the oxide solid electrolyte may include but is not limited to at least one of yttria-stabilized zirconia (YSZ) or doped cerium oxide. The sulfide solid electrolyte may include but is not limited to at least one of a lithium sulfide system or a phosphorus sulfide system. The lithium sulfide system may include but is not limited to LiPS and / or LiGePS. The phosphorus sulfide system may include but is not limited to LiPSCl and / or LiPSBr. The halide solid electrolyte may include but is not limited to lithium lanthanum fluoride (LiLaF) or lithium fluoroaluminate (Li 3 AlF 6) at least one of the following. The NASICON type solid electrolyte may include but is not limited to Li 3 Zr 2 (PO 4 ) 3 or lithium aluminum titanium phosphate (LATP). The perovskite-type solid electrolyte may include but is not limited to Li 3 La 2 / 3-x TiO 4+3x (LLTO), Li 7 La 3 Zr 2 O 12 (LLZO) or Li 6.25 Al 0.25 La 3 Zr 2 O 12 At least one of (LLZTO), wherein 0≤X≤0.5.

[0033] In some embodiments of the present application, the average particle size D of the solid electrolyte is 0.001 μm to 3.5 μm. For example, the average particle size D of the solid electrolyte can be 0.001 μm, 0.005 μm, 0.01 μm, 0.05 μm, 0.1 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm or a range consisting of any two values ​​therebetween. By regulating the average particle size D of the solid electrolyte within the above range, the porous electrolyte membrane obtained is conducive to improving the transmission efficiency of active ions, and the porous electrolyte membrane has good mechanical strength, which is conducive to improving the rate performance and structural stability of the solid-state secondary battery.

[0034] In some embodiments of the present application, the electrolyte salt is selected from at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide or lithium tetrafluoroborate. By selecting the above electrolyte salt, the solid electrolyte membrane obtained is more stable, which is conducive to widening the electrochemical window of the secondary battery and is more conducive to improving the rate performance of the solid secondary battery.

[0035] In some embodiments of the present application, the porous electrolyte membrane satisfies at least one of the following characteristics: (1) the thickness H1 of the porous electrolyte membrane is 1 μm to 4 μm; (2) the porosity P1 of the porous electrolyte membrane is 30% to 80%; (3) the average pore size d1 of the porous electrolyte membrane is 0.2 μm to 1 μm. The porous electrolyte membrane satisfies at least one of the above characteristics, which is conducive to improving the expansion rate and capacity retention rate of the solid-state secondary battery during the cycle process, and further improving the rate performance of the solid-state secondary battery.

[0036] In some embodiments of the present application, the thickness H1 of the porous electrolyte membrane is 1 μm to 4 μm; for example, the thickness H1 of the porous electrolyte membrane can be 1 μm, 1.2 μm, 1.4 μm, 1.5 μm, 1.7 μm, 1.9 μm, 2 μm, 2.2 μm, 2.4 μm, 2.5 μm, 2.7 μm, 2.9 μm, 3 μm, 3.3 μm, 3.4 μm, 3.5 μm, 3.7 μm, 3.9 μm, 4 μm or a range consisting of any two values ​​therebetween. By regulating the thickness H1 of the porous electrolyte membrane within the above range, the obtained composite current collector has suitable mechanical strength and a short transmission path for active ions, which is beneficial to improving the rate performance of the solid-state secondary battery and taking into account the cycle performance and energy density.

[0037] In some embodiments of the present application, the porosity P1 of the porous electrolyte membrane is 30% to 80%; for example, the porosity P1 of the porous electrolyte membrane can be 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80% or a range consisting of any two values ​​therebetween. By regulating the porosity P1 of the porous electrolyte membrane within the above range, the obtained composite current collector has suitable mechanical strength and is conducive to the transmission of active ions, thereby facilitating the improvement of the rate performance of the solid-state secondary battery.

[0038] In some embodiments of the present application, the average pore size d1 of the porous electrolyte membrane is 0.2 μm to 1 μm. For example, the average pore size d1 of the porous electrolyte membrane can be 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, or a range consisting of any two values ​​therebetween. By regulating the average pore size d1 of the porous electrolyte membrane within the above range, the obtained composite current collector has suitable mechanical strength and is conducive to the transmission of active ions, thereby facilitating the improvement of the rate performance of the solid-state secondary battery.

[0039] In some embodiments of the present application, the first conductive layer satisfies at least one of the following characteristics: (1) the thickness H2 of the first conductive layer is 0.1 μm to 5 μm; (2) the porosity P2 of the first conductive layer is 10% to 75%; (3) the average pore size d2 of the first conductive layer is 0.1 μm to 0.8 μm. The first conductive layer satisfies at least one of the above characteristics, which is conducive to improving the expansion rate and capacity retention rate of the solid-state secondary battery during the cycle process, and further improving the rate performance of the solid-state secondary battery.

[0040] In some embodiments of the present application, the thickness H2 of the first conductive layer is 0.1 μm to 5 μm; for example, the thickness H2 of the first conductive layer can be 0.1 μm, 0.5 μm, 1 μm, 1.3 μm, 1.5 μm, 1.7 μm, 2 μm, 2.3 μm, 2.5 μm, 2.7 μm, 3 μm, 3.3 μm, 3.5 μm, 3.7 μm, 4 μm, 4.3 μm, 4.5 μm, 4.7 μm, 5 μm or a range consisting of any two values ​​therebetween. The thickness of the first conductive layer affects the conductivity of the first conductive layer and the conductivity inside the positive electrode material layer or the negative electrode material layer adjacent thereto. The thicker the thickness of the first conductive layer, the higher the conductivity, but the lower the volume energy density of the solid-state secondary battery. By regulating the thickness H2 of the first conductive layer within the scope of the present application, it has a suitable thickness, which can make the first conductive layer have a higher conductivity while the solid-state secondary battery also has a higher volume energy density.

[0041] In some embodiments of the present application, the porosity P2 of the first conductive layer is 10% to 75%; for example, the porosity P2 of the first conductive layer can be 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75% or a range consisting of any two values ​​therebetween. By regulating the porosity P2 of the first conductive layer within the above range, it is beneficial to form an interaction force between the porous electrolyte membrane and the positive electrode material layer or the negative electrode material through the same polymer, reduce the gap between the composite current collector and the positive electrode material layer or the negative electrode material, and the obtained composite current collector is beneficial to the transmission of active ions, thereby improving the expansion rate and capacity retention rate during the cycle of the solid-state secondary battery, as well as the rate performance of the solid-state secondary battery.

[0042] In some embodiments of the present application, 0.44≤P1 / P2≤5. In some embodiments of the present application, 1≤P1 / P2≤1.5. For example, P1 / P2 can be 0.44, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5 or a range consisting of any two of these values. By having the value of P1 / P2 within the above range, it is beneficial for the porosity of the porous electrolyte membrane and the porosity of the first conductive layer to match each other, which helps to further improve the transmission rate of active ions, thereby improving the rate performance of the secondary battery. In some embodiments of the present application, the porosity of the first conductive layer is less than the porosity of the porous electrolyte membrane, and the preparation process of the composite current collector is less difficult, which is beneficial for the large-scale production of the composite current collector.

[0043] In some embodiments of the present application, the average pore size d2 of the first conductive layer is 0.1 μm to 0.8 μm. For example, the average pore size d2 of the first conductive layer can be 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm or a range consisting of any two values ​​therebetween. By regulating the average pore size d2 of the first conductive layer within the above range, it is beneficial for the porous electrolyte membrane to form an interaction force with the positive electrode material layer or the negative electrode material through the same polymer, reducing the gap between the composite current collector and the positive electrode material layer or the negative electrode material, and the obtained composite current collector is beneficial to the transmission of active ions, thereby improving the expansion rate and capacity retention rate during the cycle of the solid-state secondary battery, as well as the rate performance of the solid-state secondary battery.

[0044] In some embodiments of the present application, 0.5≤d1 / d2≤5. In some embodiments of the present application, 1≤d1 / d2≤2. For example, d1 / d2 can be 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5 or a range consisting of any two of these values. By having the value of d1 / d2 within the above range, it is beneficial for the pore size of the porous electrolyte membrane and the pore size of the first conductive layer to match each other, which helps to further improve the transmission rate of active ions, thereby improving the rate performance of the secondary battery. In some embodiments of the present application, the pore size of the first conductive layer is smaller than the pore size of the porous electrolyte membrane, and the preparation process of the composite current collector is less difficult, which is conducive to large-scale production of the composite current collector.

[0045] In some embodiments of the present application, the second conductive layer satisfies at least one of the following characteristics: (1) the thickness H3 of the second conductive layer is 0.1 μm to 5 μm; (2) the porosity P3 of the second conductive layer is 10% to 75%; (3) the average pore size d3 of the second conductive layer is 0.1 μm to 0.8 μm. The second conductive layer satisfies at least one of the above characteristics, which is conducive to improving the expansion rate and capacity retention rate of the solid-state secondary battery during the cycle process, and further improving the rate performance of the solid-state secondary battery.

[0046] In some embodiments of the present application, the thickness H3 of the second conductive layer is 0.1 μm to 5 μm; for example, the thickness H3 of the second conductive layer can be 0.1 μm, 0.5 μm, 1 μm, 1.3 μm, 1.5 μm, 1.7 μm, 2 μm, 2.3 μm, 2.5 μm, 2.7 μm, 3 μm, 3.3 μm, 3.5 μm, 3.7 μm, 4 μm, 4.3 μm, 4.5 μm, 4.7 μm, 5 μm or a range consisting of any two values ​​therebetween. The thickness of the second conductive layer affects the conductivity of the second conductive layer and the conductivity inside the positive electrode material layer or the negative electrode material layer adjacent thereto. The thicker the thickness of the second conductive layer, the higher the conductivity, but the lower the volume energy density of the solid-state secondary battery. By regulating the thickness H3 of the second conductive layer within the scope of the present application, it has a suitable thickness, which can make the second conductive layer have a higher conductivity while the solid-state secondary battery also has a higher volume energy density.

[0047] In some embodiments of the present application, the porosity P3 of the second conductive layer is 10% to 80%; for example, the porosity P3 of the second conductive layer can be 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75% or a range consisting of any two values ​​therebetween. By regulating the porosity P3 of the second conductive layer within the above range, it is beneficial to form an interaction force between the porous electrolyte membrane and the positive electrode material layer or the negative electrode material through the same polymer, reduce the gap between the composite current collector and the positive electrode material layer or the negative electrode material, and the obtained composite current collector is beneficial to the transmission of active ions, thereby improving the expansion rate and capacity retention rate during the cycle of the solid-state secondary battery, as well as the rate performance of the solid-state secondary battery.

[0048] In some embodiments of the present application, 0.44≤P1 / P3≤5. For example, P1 / P3 can be 0.44, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5 or a range consisting of any two of these values. By having the value of P1 / P3 within the above range, it is beneficial for the porosity of the porous electrolyte membrane and the porosity of the second conductive layer to match each other, which helps to further improve the transmission rate of active ions, thereby improving the rate performance of the secondary battery. In some embodiments of the present application, the porosity of the second conductive layer is less than the porosity of the porous electrolyte membrane, and the preparation process of the composite current collector is less difficult, which is conducive to the large-scale production of the composite current collector.

[0049] In some embodiments of the present application, the average pore size d3 of the second conductive layer is 0.1 μm to 0.8 μm. For example, the average pore size d3 of the second conductive layer can be 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm or a range consisting of any two values ​​therebetween. By regulating the average pore size d3 of the second conductive layer within the above range, it is beneficial to form an interaction force between the porous electrolyte membrane and the positive electrode material layer or the negative electrode material through the same polymer, reduce the gap between the composite current collector and the positive electrode material layer or the negative electrode material, and the obtained composite current collector is beneficial to the transmission of active ions, thereby improving the expansion rate and capacity retention rate during the cycle of the solid-state secondary battery, as well as the rate performance of the solid-state secondary battery.

[0050] In some embodiments of the present application, 0.5≤d1 / d3≤5. In some embodiments of the present application, 1≤d1 / d3≤2. For example, d1 / d3 can be 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5 or a range consisting of any two of these values. By having the value of d1 / d3 within the above range, it is beneficial for the pore size of the porous electrolyte membrane and the pore size of the second conductive layer to match each other, which helps to further improve the transmission rate of active ions, thereby improving the rate performance of the secondary battery. In some embodiments of the present application, the pore size of the second conductive layer is smaller than the pore size of the porous electrolyte membrane, and the preparation process of the composite current collector is less difficult, which is conducive to large-scale production of the composite current collector.

[0051] In some embodiments of the present application, the first conductive layer is disposed between the porous electrolyte membrane and the positive electrode material layer, the second conductive layer is disposed between the porous electrolyte membrane and the negative electrode material layer, and the thickness of the first conductive layer is greater than that of the second conductive layer.

[0052] In some embodiments of the present application, the first conductive layer and the second conductive layer are each independently selected from a metal layer. The material of the metal layer may include, but is not limited to, at least one of copper, aluminum, zinc, titanium, nickel or silver. The metal layer has good electrical conductivity, and the obtained composite current collector also has good electrical conductivity, which is beneficial to improve the expansion rate and capacity retention rate during the cycle of the solid-state secondary battery.

[0053] In some embodiments of the present application, the first conductive layer and the second conductive layer are each independently selected from a conductive carbon layer. The conductive carbon layer includes a conductive carbon material and a binder. The conductive carbon material may include but is not limited to at least one of conductive carbon black, carbon nanotubes or conductive graphite, and the binder may include at least one of polyvinylidene fluoride, styrene-butadiene rubber or acrylate. The conductive carbon layer has good conductive stability, is not easily oxidized and corroded during the charge and discharge cycle of the secondary battery, and has high safety. At the same time, the interface impedance between it and the positive electrode material layer or the negative electrode material is small, which is more conducive to improving the expansion rate and capacity retention rate during the cycle of the solid-state secondary battery. The present application has no special restrictions on the content of the conductive carbon material and the binder, as long as the purpose of the present application can be achieved. For example, the mass percentage of the conductive carbon material in the conductive carbon layer is 50% to 95%, and the content of the binder in the conductive carbon layer is 5% to 50%.

[0054] In some embodiments of the present application, the first conductive layer is disposed between the porous electrolyte membrane and the positive electrode material layer, the second conductive layer is disposed between the porous electrolyte membrane and the negative electrode material layer, and the first conductive layer and the second conductive layer are each independently selected from a conductive carbon layer. The mass percentage of the conductive carbon material in the first conductive layer is X1, and the mass percentage of the conductive carbon material in the second conductive layer is X2, 1≤X1 / X2<2. For example, X1 / X2 can be 1.01, 1.1, 1.2, 1.4, 1.6, 1.8, 1.9 or a range consisting of any two of the values. The conductivity of the negative electrode material layer is generally stronger than that of the positive electrode material layer, so that the content of the conductive carbon material in the first conductive layer is greater than the content of the conductive carbon material in the second conductive layer, which can make the composite electrode sheet have good conductivity as a whole.

[0055] In some embodiments of the present application, 60%≤X1≤95%, 50%≤X2≤95%.

[0056] In some embodiments of the present application, the solid-state secondary battery includes at least two composite pole pieces stacked in layers, and a solid electrolyte is disposed between two adjacent composite pole pieces. The solid-state secondary battery may include multiple composite pole pieces, and the present application does not limit the specific number of composite pole pieces, as long as the purpose of the present application can be achieved. In the present application, the solid electrolyte may be the solid electrolyte in the above-mentioned porous electrolyte membrane.

[0057] The production method of solid-state secondary batteries is usually to solidify the electrolyte solution in situ at high temperature to obtain a solid electrolyte material located between the pole pieces. Therefore, in addition to the solid electrolyte, it can also include a binder and / or an electrolyte salt between the two composite pole pieces. When the binder is selected from the polymer in the above-mentioned porous electrolyte membrane, that is, the solid-state electrolyte material and the positive electrode material layer, the solid-state electrolyte material and the negative electrode material layer contain the same polymer, so that the interaction force is formed between the two through the same polymer, which can reduce the gap between the two, and is conducive to further improving the expansion rate and capacity retention rate during the cycle of the solid-state secondary battery, as well as the rate performance of the solid-state secondary battery. The electrolyte salt can be selected from the electrolyte salt in the above-mentioned porous electrolyte membrane, which can provide active ions.

[0058] In some embodiments of the present application, the electrolyte solution includes a solid electrolyte, a binder, an electrolyte salt and a solvent. The present application does not limit the ratio of each substance, as long as the purpose of the present application can be achieved. For example, the mass ratio of the solid electrolyte, the binder, and the electrolyte salt can be (10 to 50): (40 to 80): (10 to 20). The present application does not limit the above-mentioned solvent, as long as the purpose of the present application can be achieved.

[0059] In two adjacent composite electrode sheets, the positive electrode material layer of one composite electrode sheet is adjacent to the negative electrode material layer of the other composite electrode sheet. Figure 1 As shown, a solid electrolyte 20 is arranged between two adjacent composite pole pieces 10, one side of the solid electrolyte 20 is adjacent to the positive electrode material layer 11, and the other side of the solid electrolyte 20 is adjacent to the negative electrode material layer 12, that is, the positive electrode material layer 11 of one composite pole piece 10 is adjacent to the negative electrode material layer 12 of another composite pole piece 10.

[0060] The present application has no particular restrictions on the preparation method of the porous electrolyte membrane, as long as the purpose of the present application can be achieved. For example, the preparation method of the porous electrolyte membrane may include but is not limited to the following steps: mixing a polymer, a solid electrolyte, an electrolyte salt and a solvent, and dispersing them uniformly to obtain a mixed solution. The mixed solution is poured into a mold, placed in a non-solvent and allowed to stand for 1h to 48h, so that the non-solvent penetrates into the mixed solution, changes the solubility of the mixed solution, induces phase separation, and then the mold containing the film is taken out of the non-solvent, dried to obtain a film, and then rolled to obtain a porous electrolyte membrane. Among them, the solid content of the mixed solution can be 5% to 75%. The present application does not limit the types of the above-mentioned solvents and non-solvents, as long as the purpose of the present application can be achieved. For example, the above-mentioned solvents may include but are not limited to at least one of N, N-dimethylformamide (DMF), isopropyl alcohol (IPA) or N-methylpyrrolidone (NMP), and the non-solvent may include but is not limited to at least one of ethanol, ethyl acetate, acetone, and water. The present application has no particular restrictions on the ratio of the solvent and the non-solvent, as long as the purpose of the present application can be achieved. For example, the volume ratio of the solvent and the non-solvent may be (1 to 10):1. The present application has no particular limitation on the drying temperature, as long as the purpose of the present application can be achieved. For example, the drying temperature can be 60° C. to 120° C. The present application has no particular limitation on the roller pressure, as long as the purpose of the present application can be achieved. For example, the roller pressure can be 1 MPa to 100 MPa.

[0061] The present application does not particularly limit the regulation method of the thickness of the porous electrolyte membrane, as long as the purpose of the present application can be achieved. For example, the solid content of the mixed solution, the amount of the mixed solution poured into the mold, or the pressure of the roll can be regulated. Exemplarily, the solid content of the mixed solution and the pressure of the roll are certain, the amount of the mixed solution poured into the mold increases, and the thickness of the porous electrolyte membrane increases, otherwise it decreases; the amount of the mixed solution poured into the mold and the pressure of the roll are certain, the solid content of the mixed solution increases, and the thickness of the porous electrolyte membrane increases, otherwise it decreases; the solid content of the mixed solution and the amount of the mixed solution poured into the mold are certain, the pressure of the roll increases, and the thickness of the porous electrolyte membrane increases, otherwise it decreases.

[0062] The present application does not particularly limit the method for regulating the porosity of the porous electrolyte membrane, as long as the purpose of the present application can be achieved. For example, it can be regulated by the drying temperature and the roller pressure. For example, when the drying temperature is constant, the roller pressure increases, and the porosity of the porous electrolyte membrane decreases, and vice versa. When the roller pressure is constant, the drying temperature increases, and the porosity of the porous electrolyte membrane decreases, and vice versa.

[0063] The present application does not particularly limit the method for regulating the pore size of the porous electrolyte membrane, as long as the purpose of the present application can be achieved. For example, the type and ratio of the solvent and the non-solvent can be controlled to control the phase separation process during drying. For example, as the volume ratio of the solvent to the non-solvent increases, the pore size of the porous electrolyte membrane decreases, and vice versa; the pore size of the porous electrolyte membrane varies depending on the type of solvent and non-solvent.

[0064] The first conductive layer and the second conductive layer are metal layers. The present application has no particular restrictions on the preparation method of the composite current collector, as long as the purpose of the present application can be achieved. For example, the preparation method of the composite current collector may include but is not limited to the following steps: a first conductive layer is arranged on one surface of a porous electrolyte membrane by magnetron sputtering, and a second conductive layer is arranged on another surface of the porous electrolyte membrane by magnetron sputtering. The thickness of the first conductive layer is mainly regulated by the amount of metal sputtered by magnetron sputtering. When the amount of metal increases, the thickness of the first conductive layer increases, and vice versa. The thickness of the second conductive layer can be regulated with reference to the regulation method of the thickness of the first conductive layer. The porosity and pore size of the first conductive layer mainly depend on the metal sputtering rate per unit time of magnetron sputtering. For example, the metal sputtering rate per unit time increases, the porosity and pore size of the first conductive layer decrease, and vice versa. The porosity and pore size of the second conductive layer can be regulated with reference to the regulation method of the porosity and pore size of the first conductive layer.

[0065] The first conductive layer and the second conductive layer are conductive carbon layers. The present application does not specifically limit the preparation method of the composite current collector, as long as the purpose of the present application can be achieved. For example, the preparation method of the composite current collector may include but is not limited to the following steps: uniformly mixing the conductive carbon material, the binder and the solvent to obtain a conductive carbon layer slurry; coating the conductive carbon layer slurry on one surface of the porous electrolyte membrane, and drying to obtain the first conductive layer; coating the conductive carbon layer slurry on the other surface of the porous electrolyte membrane, and drying to obtain the second conductive layer. Among them, the solid content of the conductive carbon layer slurry can be 0.5% to 5%. The present application does not limit the above solvent, as long as the purpose of the present application can be achieved. For example, the above solvent may include but is not limited to at least one of water, N-methylpyrrolidone (NMP) or N,N-dimethylformamide (DMF). It can be understood that the conductive carbon materials in the first conductive layer and the second conductive layer may be the same or different, and the binders in the first conductive layer and the second conductive layer may be the same or different.

[0066] The first conductive layer and the second conductive layer are conductive carbon layers. The thickness of the first conductive layer can be controlled by adjusting the solid content and coating amount of the conductive carbon layer slurry. When the solid content of the conductive carbon layer slurry is constant, the coating amount is increased, and the thickness of the first conductive layer increases, otherwise it decreases; when the coating amount of the conductive carbon layer slurry is constant, the solid content is increased, and the thickness of the first conductive layer increases, otherwise it decreases. The thickness of the second conductive layer can be controlled by referring to the control method of the thickness of the first conductive layer.

[0067] The first conductive layer and the second conductive layer are conductive carbon layers. The porosity and pore size of the first conductive layer are related to the porosity and pore size of the porous electrolyte membrane. At the same time, the porosity and pore size of the first conductive layer can be adjusted by adjusting the coating parameters of the conductive carbon layer slurry, the viscosity of the conductive carbon layer slurry, etc. Specifically, the conductive carbon layer slurry can be coated by gravure coating, and the porosity and pore size of the first conductive layer can be adjusted by adjusting the specifications of the gravure. When the solid content of the conductive carbon layer slurry is constant, the viscosity of the conductive carbon layer slurry can be adjusted by adding a dispersant. For example, when the viscosity of the conductive carbon layer slurry increases, the porosity and pore size of the first conductive layer decrease, and vice versa. The porosity and pore size of the second conductive layer can be regulated by referring to the regulation method of the porosity and pore size of the first conductive layer.

[0068] The present application does not have any particular restrictions on the preparation method of the composite electrode sheet, as long as the purpose of the present application can be achieved. For example, the preparation method of the composite electrode sheet may include but is not limited to the following steps: preparing a positive electrode material layer slurry, preparing a negative electrode slurry material layer; coating the positive electrode material layer slurry on one surface of the composite current collector, drying, to obtain a composite current collector provided with a positive electrode material layer; coating the negative electrode material layer slurry on the other surface of the composite current collector, drying, to obtain a composite electrode sheet. The thickness of the positive electrode material layer can be regulated by regulating the solid content and coating amount of the positive electrode material layer slurry. If the solid content of the positive electrode material layer slurry is constant, increasing the coating amount will increase the thickness of the positive electrode material layer, and vice versa; if the coating amount of the positive electrode material layer slurry is constant, increasing the solid content will increase the thickness of the positive electrode material layer, and vice versa. The thickness of the negative electrode material layer can be regulated by referring to the regulation method of the thickness of the positive electrode material layer.

[0069] In the present application, the positive electrode material layer includes a positive electrode active material. The present application has no particular limitation on the positive electrode active material as long as the purpose of the present application can be achieved. For example, the positive electrode active material may include but is not limited to lithium nickel cobalt manganese oxide (such as NCM811, NCM622, NCM523, NCM111), lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide (LiCoO 2 ), at least one of lithium manganese oxide, lithium iron manganese phosphate or lithium titanate.

[0070] The positive electrode material layer may also include a positive electrode conductor and a positive electrode binder. The present application does not particularly limit the types of the positive electrode conductor and the positive electrode binder, as long as the purpose of the present application can be achieved. For example, the positive electrode conductor may include but is not limited to at least one of conductive carbon black (Super P), carbon nanotubes (CNTs), carbon fibers, flake graphite, graphene, metal materials or conductive polymers, and the conductive carbon black may include but is not limited to at least one of acetylene black or Ketjen black. The above-mentioned carbon nanotubes may include but are not limited to single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The above-mentioned carbon fibers may include but are not limited to vapor-grown carbon fibers (VGCF) and / or nano-carbon fibers. The above-mentioned metal materials may include but are not limited to metal powders and / or metal fibers. Specifically, the metal may include but is not limited to at least one of copper, nickel, aluminum or silver. The above-mentioned conductive polymer may include but is not limited to at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene or polypyrrole. The positive electrode binder may include, but is not limited to, at least one of polyacrylic acid, sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyimide, polyvinyl alcohol, carboxymethyl cellulose, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, polyimide, polyamide-imide, styrene-butadiene rubber or polyvinylidene fluoride. The present application does not particularly limit the mass ratio of the positive electrode active material, the positive electrode conductive agent and the positive electrode binder in the positive electrode material layer, and those skilled in the art may select according to actual needs, as long as the purpose of the present application can be achieved.

[0071] The present application has no particular limitation on the thickness of the positive electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the positive electrode material layer can be 25 μm to 180 μm.

[0072] In the present application, the negative electrode material layer includes a negative electrode active material. The present application has no particular limitation on the negative electrode active material as long as the purpose of the present application can be achieved. For example, the negative electrode active material may include but is not limited to natural graphite, artificial graphite, mesophase microcarbon beads, hard carbon, soft carbon, silicon, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO 2 , spinel-structured lithiated TiO 2 -Li 4 Ti 5 O 12 Or at least one of Li-Al alloy.

[0073] In some embodiments of the present application, the negative electrode material layer may further include a negative electrode conductive agent and a negative electrode binder. The present application does not particularly limit the types of the negative electrode conductive agent and the negative electrode binder, as long as the purpose of the present application can be achieved. For example, it may be at least one of the above-mentioned positive electrode conductive agent and the above-mentioned positive electrode binder. The present application does not particularly limit the mass ratio of the negative electrode active material, the negative electrode conductive agent, and the negative electrode binder in the negative electrode material layer. Those skilled in the art may select according to actual needs, as long as the purpose of the present application can be achieved.

[0074] The present application has no particular limitation on the thickness of the negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the negative electrode material layer may be 30 μm to 300 μm.

[0075] The present application does not have any particular restrictions on the preparation method of the solid-state secondary battery, as long as the purpose of the present application can be achieved. For example, the preparation method of the solid-state secondary battery may include but is not limited to the following steps: (1) mixing the solid electrolyte, the binder and the solvent evenly to obtain an electrolyte solution; (2) stacking the composite pole pieces to obtain an electrode assembly of a laminated structure, or stacking and winding the composite pole pieces to obtain an electrode assembly of a wound structure, and loading it into a shell; (3) injecting the electrolyte solution into the shell containing the electrode assembly according to the specification of 1.2g / Ah to 1.4g / Ah; (4) allowing the electrolyte solution to penetrate the electrode assembly at room temperature, and after 48 hours of penetration, the electrode assembly is basically completely penetrated, and then heat-treated and sealed to obtain a solid-state secondary battery. The present application does not have any particular restrictions on the time and temperature of the heat treatment, as long as the purpose of the present application can be achieved. For example, the heat treatment temperature can be 45°C to 120°C and the time can be 12h to 72h.

[0076] The present application has no particular restrictions on the housing, and it can be a housing known in the art, as long as it can achieve the purpose of the present application. For example, the housing can be a hard shell housing or a flexible shell. The material of the hard shell housing can be metal, and the present application does not limit the type of metal, and a metal hard shell housing known in the art can be used, as long as it can achieve the purpose of the present application. The flexible shell can be a metal plastic film, such as an aluminum plastic film, a steel plastic film, etc.

[0077] The second aspect of the present application provides an electric device, which includes the solid-state secondary battery in any of the above embodiments. Therefore, the electric device provided by the present application has good performance.

[0078] The present application does not particularly limit the type of electrical device, and it can be used for any electrical device known in the prior art. In some embodiments of the present application, the electrical device may include, but is not limited to, a notebook computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, a liquid crystal television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.

[0079] Example Hereinafter, the embodiments of the present application will be described in more detail with reference to Examples and Comparative Examples. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are by mass.

[0080] Test methods and equipment: Rate performance test: The kinetic improvement effect on solid-state lithium-ion batteries is characterized by testing the capacity retention rate at different rates.

[0081] At 25°C, the solid-state lithium-ion battery is charged to 4.5V at 1C, then charged at 4.5V at a constant voltage to a current of 0.05C, left to stand for 5 minutes, and discharged at a constant current of 0.2C to a voltage of 3.0V. The discharge capacity of the solid-state lithium-ion battery at this time is recorded as C0; then the solid-state lithium-ion battery is charged to 4.5V at 1C, then charged at 4.5V at a constant voltage to a current of 0.05C, left to stand for 5 minutes, and discharged at a constant current of 0.5C to a voltage of 3.0V ... and then charged at 4.5V at a constant voltage to a current of 0.05C, left to stand for 5 minutes, and discharged at a constant current of 0.5C to a voltage of Charge at constant voltage until the current is 0.05C, let it stand for 5 minutes, and discharge at a constant current of 1C to a voltage of 3.0V; then charge the solid-state lithium-ion battery at 1C to 4.5V, and then charge at constant voltage at 4.5V to a current of 0.05C, let it stand for 5 minutes, and discharge at a constant current of 2C to a voltage of 3.0V; then charge the solid-state lithium-ion battery at 1C to 4.5V, and then charge at constant voltage at 4.5V to a current of 0.05C, let it stand for 5 minutes, and discharge at a constant current of 3C to a voltage of 3.0V. The discharge capacity of the solid-state lithium-ion battery at this time is recorded as C4.

[0082] 3C discharge capacity retention rate (%) = C4 / C0×100%.

[0083] Cycle performance test: At 25°C, the solid-state lithium-ion battery was charged and discharged for the first time. The specific steps were: charging at a constant current of 0.2C to a cut-off voltage of 4.5V, then charging at a constant voltage of 4.5V until the current reached 0.05C. After standing for 5 minutes, the battery was discharged at a constant current of 0.2C to a cut-off voltage of 3.0V. The discharge capacity of the solid-state lithium-ion battery was measured to be C0, which was one charge and discharge cycle.

[0084] Then, 500 cycles of charge and discharge were performed according to the above steps in an environment of 25° C., and the discharge capacity of the solid-state lithium-ion battery at the 500th cycle was measured to be C1. The cycle capacity retention rate was calculated according to the following formula.

[0085] 500-cycle capacity retention rate (%) = C1 / C0×100%.

[0086] The larger the value of the cycle capacity retention rate obtained from the test, the better the cycle performance of the solid-state lithium-ion battery.

[0087] The thickness of the solid-state lithium-ion battery before cycling is recorded as T0, and the thickness after 500 cycles is recorded as T1. The calculation formula of the cycle expansion rate is: cycle expansion rate (%) = (T1-T0) / T0×100%.

[0088] Acquisition of composite current collector samples and porous electrolyte membrane samples: The solid-state lithium-ion battery was discharged to 3V at a constant current of 0.5C, the solid-state lithium-ion battery was disassembled, the composite electrode was taken out, the positive electrode material layer and the negative electrode material layer on the surface were immersed in N-methylpyrrolidone (NMP) solution at room temperature for 30 minutes, and then the composite electrode was wiped with dust-free paper to remove the positive electrode material layer and the negative electrode material layer on the surface of the composite electrode, and then ultrasonically cleaned in NMP solution for 30 minutes at an ultrasonic frequency of 80 Hz to obtain a composite current collector.

[0089] The composite current collector is cleaned by plasma to remove the first conductive layer and the second conductive layer, thereby obtaining a porous electrolyte membrane.

[0090] Unless otherwise specified, the following test methods all use the composite current collector and porous electrolyte membrane obtained above.

[0091] Thickness test: The cross section of the composite current collector is polished by argon ion polishing technology, and then a scanning electron microscope is used to take a picture of the cross section. The thickness H1 of the porous electrolyte membrane can be measured based on the picture of the cross section.

[0092] The cross-section of the composite current collector is photographed by X-ray tomography, and the thickness H2 of the first conductive layer and the thickness H3 of the second conductive layer can be measured based on the cross-section photograph.

[0093] When measuring thickness, measure 10 locations randomly and take the average value as the final result.

[0094] Pore ​​size test (porous electrolyte membrane, first conductive layer and second conductive layer): The porous electrolyte membranes of the embodiments and comparative examples were characterized by scanning electron microscopy (SEM), and the magnification of SEM characterization was 10,000 times. The pore size of the porous electrolyte membrane was measured by observing the microstructure of the surface of the porous electrolyte membrane. In a field of view of 10 μm×10 μm, 15 holes were randomly selected, and their pore sizes were measured, and the average value was taken as the final result.

[0095] The composite current collectors of the embodiment and the comparative example were characterized by SEM, and the magnification of SEM characterization was 10000 times. The pore size of the first conductive layer was measured by observing the microstructure of the surface of the composite current collector provided with the first conductive layer. In the field of view of 10μm×10μm, 15 holes were randomly selected, and their pore sizes were measured, and the average value was taken as the final result. The pore size of the second conductive layer can be measured by observing the microstructure of the surface of the composite current collector provided with the second conductive layer.

[0096] The above-mentioned apertures are all diameters of the circumscribed circles of the respective holes.

[0097] Porosity test of porous electrolyte membrane, first conductive layer and second conductive layer: Porosity = (apparent volume of sample - true volume of sample) / apparent volume of sample; Apparent volume of the sample: Use a solid mold (5 cm × 10 cm) with an area of ​​S1 to punch out and measure the thickness h of the sample to obtain the apparent volume V of the sample. S = S1 × h; True volume of the sample: The test principle is to use the Archimedean principle of gas displacement through the gas displacement method, and use the Bohr law (PV=nRT) of inert gas with small molecular diameter under certain conditions to accurately measure the true volume of the sample being tested. Take the punched sample above, place it in the true density tester, close the test system, and introduce helium according to the procedure. By detecting the gas pressure in the sample chamber and the expansion chamber, the true volume is calculated according to Bohr's law: (1) P 1 (V cell -V samp ) =n c RT a ; (2) P a V exp = n e RT a ; When the valve is opened, the pressure drops to the middle value P 2, the mass conservation at this time becomes: (3)P 2 (V cell -V samp +V exp = n c RT a +n e RT a ; Then the actual volume of the sample is: (4) V samp =(V cell -V exp ) × (P 2 -P a ) / (P 1 -P 2 ); Among them, n c is the molar mass of the gas in the sample cup; n e is the molar mass of the gas in the expanding gas; R is the ideal gas constant; T a is the ambient temperature; V cell is the volume of the sample cup, V samp is the true volume of the sample; V exp is the volume of the expansion chamber; P 1 is the gas pressure in the sample chamber, P 2 is the equilibrium pressure of the gas after diffusion throughout the system, P a is the pressure of the gas in the expansion chamber.

[0098] The volume V0 and porosity P0 of the composite current collector, and the volume V1 and porosity P1 of the porous electrolyte membrane were measured in the above manner.

[0099] When the composite current collector includes a porous electrolyte membrane and a first conductive layer disposed on one surface of the porous electrolyte membrane, the porosity of the first conductive layer P2 (%) = (P0 × V0 - P 1 ×V1) / (V0-V1); when the composite current collector includes a porous electrolyte membrane and a second conductive layer disposed on one surface of the porous electrolyte membrane, the porosity of the second conductive layer P3 (%) = (P0×V0- P 1 ×V1) / (V0-V1); When the composite current collector includes a porous electrolyte membrane, a first conductive layer and a second conductive layer, the porous electrolyte membrane is arranged between the first conductive layer and the second conductive layer, the volume V0 and the porosity P0 of the composite current collector are measured by the above method; the second conductive layer is then removed by plasma cleaning to obtain the porous electrolyte membrane and the first conductive layer, and the volume V1' and the porosity P1' of the porous electrolyte membrane and the first conductive layer are measured; then the porosity P3 (%) of the second conductive layer is = (P0 × V0-P1' × V1') / (V0-V1'); the first conductive layer is then removed by plasma cleaning to obtain the porous electrolyte membrane, and the volume V1 and the porosity P1 of the porous electrolyte membrane are measured; then the porosity P2 (%) of the first conductive layer is = (P1' × V1'- ​​P1 × V1) / (V1'-V1).

[0100] Particle size test: Under a scanning electron microscope, at a voltage of 10KV, a view with a size of 30,000 times was selected, and 5 solid electrolyte particles were randomly selected to measure their particle sizes, and the average value was taken as the average particle size of the solid electrolyte particles.

[0101] Example 1 <Preparation of Composite Current Collector> The polymer polyacrylonitrile (PAN) was added to the DMF solvent and dissolved by ultrasonication for 30 min. Then, the solid electrolyte LLZO powder with a particle size D of 0.5 μm was added to the above solution. The mass ratio of PAN to LLZO was 63:22. Then, the electrolyte salt LiPF was added. 6 , continue ultrasonication for 30 minutes, disperse evenly, and obtain a mixed solution with a solid content of 50%. The mixed solution is poured into a mold to initially form a film, and then immersed in anhydrous ethanol and kept at room temperature for 12 hours, waiting for the non-solvent ethanol to penetrate into the mixed solution, change the solubility of the mixed solution, and induce phase separation. Among them, the volume ratio of DMF and anhydrous ethanol used in the preparation process is 6:4. Then the mold with the film is taken out of the anhydrous ethanol and vacuum dried at 80℃ for 12 hours, and the solvent is evaporated to obtain a film with a thickness of 5μm. The film is rolled to obtain a porous electrolyte membrane with a thickness of H1 of 3μm, a porosity of P1=50%, and a pore size of d1=0.5μm. Among them, the mass percentage of the solid electrolyte W1 is 22%, the mass percentage of the polymer W2 is 63%, and the mass percentage of the electrolyte salt W3 is 15%; the size of the porous electrolyte membrane is 42mm×49.2mm.

[0102] Al and Cu are respectively disposed on the two surfaces of the porous electrolyte film by magnetron sputtering to obtain a composite current collector. Among them, the Al metal layer is used as the first conductive layer, the thickness of the first conductive layer is H2 = 3μm, the porosity is P2 = 45%, and the pore size is d2 = 0.35μm; the Cu metal layer is used as the second conductive layer, the thickness of the second conductive layer is H3 = 2μm, the porosity is P3 = 45%, and the pore size is d3 = 0.35μm.

[0103] <Preparation of composite pole piece> The positive electrode active material LiCoO 2 Conductive agent conductive carbon black, and positive electrode binder polyacrylonitrile are mixed in a mass ratio of 94.8:2.8:2.4, N-methylpyrrolidone (NMP) is added as a solvent, and a slurry with a solid content of 75wt% is prepared. After vacuum stirring, the positive electrode slurry is obtained.

[0104] The negative electrode active material artificial graphite, the negative electrode dispersant sodium carboxymethyl cellulose (CMC-Na), and the negative electrode binder polyacrylonitrile were mixed in a weight ratio of 95:2:3, deionized water was added as a solvent, and the mixture was stirred and mixed to obtain a negative electrode slurry, wherein the solid content of the negative electrode slurry was 75wt%.

[0105] The positive electrode slurry was evenly coated on the surface of the first conductive layer of the composite current collector prepared above, dried at 120°C, and cold pressed to obtain a composite current collector coated with a positive electrode material layer. The compaction density of the positive electrode material layer was 4.15 g / cm 2 The negative electrode slurry was evenly coated on the surface of the second conductive layer of the composite current collector prepared above, dried at 120°C, and cold pressed. The compaction density of the negative electrode material layer was 1.75 g / cm 2 , a composite electrode sheet is obtained, wherein the thickness of the positive electrode material layer is 200 μm, and the thickness of the negative electrode material layer is 112 μm.

[0106] <Preparation of solid-state lithium-ion batteries> PAN and Li 6.25 Al 0.25 La 3 Zr 2 O 12 (LLZTO) was mixed in a mass ratio of 7:3, added to NMP, and then added to LiPF 6 , and stirred to mix evenly to obtain an electrolyte solution with a solid content of 30 wt%.

[0107] The composite pole pieces are stacked to obtain a laminated structure electrode assembly, which is then loaded into an aluminum-plastic film packaging bag. The electrolyte solution is injected into the aluminum-plastic film packaging bag and allowed to stand at room temperature for 48 hours. After the electrolyte solution is completely infiltrated into the interior of the composite pole piece, it is hot-pressed at a temperature of 45°C and a pressure of 1.3 MPa, and then heat-treated at 60°C for 24 hours to solidify the electrolyte solution in situ, and sealed to obtain a solid-state secondary battery.

[0108] Example 2 to Example 20 Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1.

[0109] Example 21 to Example 27 Except for adjusting the relevant preparation parameters according to Table 2, the rest is the same as Example 1.

[0110] Embodiment 28 Except for preparing the composite current collector according to the following steps, the rest is the same as Example 1: The preparation of the porous electrolyte membrane is the same as that of Example 1.

[0111] Mix carbon nanotubes and adhesive styrene butadiene rubber in a mass ratio of 9:1, add deionized water to prepare a slurry with a solid content of 15%, and stir evenly to obtain a first conductive layer slurry. The first conductive layer slurry is coated on one surface of the porous electrolyte membrane by gravure coating and dried. Then, the first conductive layer is used as the second conductive layer slurry, and is coated on the other surface of the porous electrolyte membrane by gravure coating, and dried to obtain a composite current collector. The first conductive layer and the second conductive layer are conductive carbon layers, the thickness of the first conductive layer is H2 = 3μm, the porosity is P2 = 45%, and the pore size is d2 = 0.35μm, and the thickness of the second conductive layer is H3 = 2μm, the porosity is P3 = 45%, and the pore size is d3 = 0.35μm.

[0112] Embodiment 29 The above method is the same as Example 28 except that the mass ratio of carbon nanotubes to adhesive in the first conductive layer slurry is 75:25, the mass ratio of carbon nanotubes to adhesive in the second conductive layer slurry is 1:1, H2=1 μm, H3=1 μm.

[0113] Example 30 to Example 36 Except for adjusting the relevant preparation parameters according to Table 3, the rest is the same as Example 1.

[0114] Comparative Example 1 Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1.

[0115] The preparation parameters and performance tests of various embodiments and comparative examples are shown in Tables 1 to 3.

[0116] Table 1

[0117] It can be seen from Examples 1 to 20 and Comparative Example 1 that the solid-state lithium-ion batteries in the examples include the composite pole piece in the present application, and the solid-state lithium-ion battery in Comparative Example 1 does not include the composite pole piece in the present application. The solid-state lithium-ion batteries in the examples have higher cycle capacity retention rate and 3C rate performance retention rate, and lower cycle expansion rate, which means that while the solid-state lithium-ion batteries in the examples have improved rate performance, the expansion rate and capacity retention rate during the cycle are also improved.

[0118] The composition of the polymer usually affects the rate performance and cycle performance of the solid-state lithium-ion battery. It can be seen from Examples 1 to 5 that when the type of polymer is within the scope of the present application, the obtained solid-state lithium-ion battery has a higher cycle capacity retention rate and 3C rate performance retention rate, and a lower cycle expansion rate. That is, by selecting a polymer within the scope of the present application, the solid-state lithium-ion battery improves the rate performance while also improving the expansion rate and capacity retention rate during the cycle.

[0119] The composition of the porous electrolyte membrane usually affects the rate performance and cycle performance of the solid-state lithium-ion battery. It can be seen from Examples 6 to 11 that when the mass percentage of the solid electrolyte, polymer, and electrolyte salt is within the scope of the present application, the obtained solid-state lithium-ion battery has a higher cycle capacity retention rate and 3C rate performance retention rate, and a lower cycle expansion rate. That is, when the above parameters are within the scope of the present application, the solid-state lithium-ion battery improves the rate performance while also improving the expansion rate and capacity retention rate during the cycle.

[0120] The thickness, porosity and pore size of the porous electrolyte membrane usually affect the rate performance and cycle performance of the solid-state lithium-ion battery. It can be seen from Examples 12 to 20 that when the thickness, porosity and pore size of the porous electrolyte membrane are within the scope of the present application, the obtained solid-state lithium-ion battery has a higher cycle capacity retention rate and 3C rate performance retention rate, and a lower cycle expansion rate. That is, when the above parameters are within the scope of the present application, the solid-state lithium-ion battery improves the rate performance while also improving the expansion rate and capacity retention rate during the cycle.

[0121] Table 2

[0122] The thickness, porosity and pore size of the first conductive layer and the second conductive layer usually affect the rate performance and cycle performance of the solid-state lithium-ion battery. It can be seen from Examples 1 and 21 to 27 that when the thickness, porosity and pore size of the first conductive layer and the second conductive layer are within the scope of the present application, the obtained solid-state lithium-ion battery has a higher cycle capacity retention rate and 3C rate performance retention rate, and a lower cycle expansion rate. That is, when the above parameters are within the scope of the present application, the solid-state lithium-ion battery improves the rate performance while also improving the expansion rate and capacity retention rate during the cycle.

[0123] The types of the first conductive layer and the second conductive layer usually affect the rate performance and cycle performance of the solid-state lithium-ion battery. It can be seen from Example 1 and Example 28 to Example 29 that when the types of the first conductive layer and the second conductive layer are within the scope of the present application, the obtained solid-state lithium-ion battery has a higher cycle capacity retention rate and 3C rate performance retention rate, and a lower cycle expansion rate. That is, the above parameters are within the scope of the present application. While the solid-state lithium-ion battery improves the rate performance, the expansion rate and capacity retention rate during the cycle are also improved.

[0124] Table 3

[0125] The type and particle size of the solid electrolyte usually affect the rate performance and cycle performance of the solid-state lithium-ion battery. It can be seen from Example 1 and Example 30 to Example 34 that when the type and particle size of the solid-state electrolyte are within the scope of the present application, the obtained solid-state lithium-ion battery has a higher cycle capacity retention rate and 3C rate performance retention rate, and a lower cycle expansion rate. That is, when the above parameters are within the scope of the present application, the solid-state lithium-ion battery improves the rate performance while also improving the expansion rate and capacity retention rate during the cycle.

[0126] It can be seen from Example 1 and Example 35 to Example 36 that when the binder in the positive electrode material layer and / or the negative electrode material layer is the same as the polymer in the porous electrolyte membrane, the obtained solid-state lithium ion battery has a high cycle capacity retention rate and 3C rate performance retention rate and a low cycle expansion rate. That is, the binder of at least one of the positive electrode material layer and the negative electrode material layer is the same as the polymer in the porous electrolyte membrane, which can achieve the improvement of the solid-state lithium ion battery's rate performance while also improving the expansion rate and capacity retention rate during the cycle.

[0127] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method or article including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method or article.

[0128] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.

Claims

1. A solid-state secondary battery, comprising a composite electrode sheet, the composite electrode sheet comprising a positive electrode material layer, a negative electrode material layer and a composite current collector located between the positive electrode material layer and the negative electrode material layer, the composite current collector comprising a porous electrolyte membrane and a first conductive layer and a second conductive layer respectively located on two surfaces of the porous electrolyte membrane; The porous electrolyte membrane includes a solid electrolyte, a polymer and an electrolyte salt, and the positive electrode material layer and / or the negative electrode material layer includes the polymer.

2. The solid-state secondary battery according to claim 1, wherein: The polymer is selected from at least one of polyvinylidene fluoride, polyethylene oxide, polyacrylonitrile or polymethyl methacrylate.

3. The solid-state secondary battery according to claim 1, wherein: Based on the mass of the porous electrolyte membrane, the mass percentage W1 of the solid electrolyte is 10% to 50%, the mass percentage W2 of the polymer is 40% to 80%, and the mass percentage W3 of the electrolyte salt is 10% to 20%.

4. The solid-state secondary battery according to any one of claims 1 to 3, wherein: The solid electrolyte is selected from at least one of an oxide solid electrolyte, a sulfide solid electrolyte, a halide solid electrolyte, a NASICON solid electrolyte or a perovskite solid electrolyte.

5. The solid-state secondary battery according to any one of claims 1 to 3, wherein: The average particle size D of the solid electrolyte is 0.001 μm to 3.5 μm.

6. The solid-state secondary battery according to any one of claims 1 to 3, wherein: The electrolyte salt is selected from at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, and lithium tetrafluoroborate.

7. The solid-state secondary battery according to any one of claims 1 to 3, wherein: The porous electrolyte membrane satisfies at least one of the following characteristics: (1) The thickness H1 of the porous electrolyte membrane is 1 μm to 4 μm; (2) The porosity P1 of the porous electrolyte membrane is 30% to 80%; (3) The average pore diameter d1 of the porous electrolyte membrane is 0.2 μm to 1 μm.

8. The solid-state secondary battery according to any one of claims 1 to 3, wherein: The first conductive layer satisfies at least one of the following characteristics: (1) The thickness H2 of the first conductive layer is 0.1 μm to 5 μm; (2) The porosity P2 of the first conductive layer is 10% to 75%; (3) The average pore diameter d2 of the first conductive layer is 0.1 μm to 0.8 μm.

9. The solid-state secondary battery according to any one of claims 1 to 3, wherein: The second conductive layer satisfies at least one of the following characteristics: (1) The thickness H3 of the second conductive layer is 0.1 μm to 5 μm; (2) The porosity P3 of the second conductive layer is 10% to 75%; (3) The average pore diameter d3 of the second conductive layer is 0.1 μm to 0.8 μm.

10. The solid-state secondary battery according to any one of claims 1 to 3, wherein: The first conductive layer and the second conductive layer are each independently selected from a metal layer or a conductive carbon layer.

11. A solid-state secondary battery according to any one of claims 1 to 3, comprising at least two stacked composite pole sheets, with a solid electrolyte disposed between two adjacent composite pole sheets; in two adjacent composite pole sheets, the positive electrode material layer of one composite pole sheet is adjacent to the negative electrode material layer of the other composite pole sheet. 12 . An electrical device comprising the solid-state secondary battery according to claim 1 .